The AIDS Clinical Trials Information Service (ACTIS): a decade of providing clinical trials information. - Katz, Deborah G. (Association of Schools of Public Health, 2002)
The AIDS Clinical Trials Information Service (ACTIS) is a central resource for information about federally and privately funded HIV/AIDS clinical trials. Sponsored by four components of the U.S. Department of Health and Human Services, ACTIS has been a key part of U.S. HIV/AIDS information and education services since 1989. ACTIS offers a toll-free telephone service, through which trained information specialists can provide callers with information about AIDS clinical trials in English or Spanish, and a website that provides access to clinical trials databases and a variety of educational resources. Future priorities include the development of new resources to target diverse and underserved populations. In addition, research needs to be conducted on the use of telephone services vs. Web-based information exchange to ensure the broadest possible dissemination of up-to-date information on HIV infection and clinical trials.